Frequency emergency control method considering the plug-in electric vehicles aggregator load shedding. (October 2019) - Rao, D Q; Hou, M J; Luo, T; Fang, S L
Abstract: The Plug-In Electric Vehicle (PEV) has fast response characteristics. In this paper, it is used for emergency control of power system frequency in Vehicle to Grid (V2G) mode. The power system frequency dynamics assessment method is given based on PEV aggregator and single machine equivalent model. The PEV aggregator-based system frequency emergency control framework is established, and the main components and scope of the framework are described. A calculation method based on dispatchable PEV load shedding is proposed. The method injects power into the system through V2G mode to balance the Power shortages on the basis of guaranteeing the quality of power system services and the charging demand of PEV users. The simulation results show that the proposed method can cut the load without cutting or under load on the premise of ensuring the target frequency.